Kewarganegaraan dan Perlindungan HAM di Era Globalisasi - Musthofa Husni Mukti; Muhammad Ghozi Alfaruq; Muhammad Rizki Ar Ridho; Fayi' Ahmad Faiq (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
The era of globalization has introduced new dynamics in the practice of citizenship and the protection of human rights (HR), both at national and international levels. The background of this study stems from the increasing flow of migration, the rapid development of information technology, and the interconnectedness of global economic and political systems, all of which challenge the traditional concept of citizenship and mechanisms for protecting HR. The aim of this research is to analyze the relevance of citizenship in the context of globalization and to examine the effectiveness of human rights protection in addressing cross-border issues. The method employed is a literature study with a qualitative-descriptive approach, drawing on academic sources, international legal instruments, and national regulations concerning citizenship and HR. The findings indicate that globalization expands the scope of citizen participation, but simultaneously creates new vulnerabilities, such as discrimination against migrants, weak digital protection, and gaps in access to justice. On the other hand, international legal instruments and the role of transnational organizations have shown potential in strengthening protection, although their implementation still faces challenges at the domestic level. In conclusion, citizenship in the globalization era is no longer limited to a legal-formal identity, but also encompasses universal rights that demand states to enhance global collaboration, regulatory harmonization, and policy innovation in human rights protection.